The Use of Fluoroquinolones for Tuberculosis in Victoria between 2011 and 2016. (2nd July 2018) - Murray, Hugh; Tay, Ee Laine; Dinh, Sarah; Matthews, Helen; Street, Alan; Denholm, Justin T.
Abstract : Setting. Tuberculosis treatment requires long regimens with multiple antibiotics and is complicated by antibiotic resistance and intolerance. Fluoroquinolones were introduced for the treatment of multidrug resistant TB and have become a vital part of therapy. Objective. Reviewing the indications for fluoroquinolones use in the treatment of active TB in Victoria, Australia. Design. This was a retrospective case-control study of Victorian patients prescribed fluoroquinolones for active tuberculosis, from January 2011 to December 2016. Indications for fluoroquinolone use were extracted from an existing public health database. Results. There were 2268 patients notified to have tuberculosis in Victoria between 2011 and 2016, 276 (12.2%) of whom received a fluoroquinolone. The indications were substitution when intolerance was present (33.3%) or anticipated (21.0%), proven drug resistance (22.5%), suspected drug resistance (13.0%), and site of disease (10.1%). Where fluoroquinolones were prescribed for suspected drug resistance, only a minority of isolates (13%) had resistance confirmed. Conclusion. Fluoroquinolones were most commonly used as replacement for first-line therapy related to adverse effects, when either present or anticipated. Where fluoroquinolones were prescribed for suspected drug resistance, only a minority of isolates ultimately had resistance confirmed. These findings reinforce the importance of fluoroquinolones in TB therapy and the need for ongoing pharmacovigilance to ensure appropriate use.